Olefin polymerization catalyst component as well as preparation method, catalyst system and application thereof
By using long-chain α-olefins to treat the catalyst components, a spherical catalyst with high activity and intact particle shape is formed, which solves the problems of complex processes, large energy consumption and difficult particle shape in the prior art, and achieves an efficient olefin polymerization effect.
Patent Information
- Application Number
- CN202311385372.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-10-24
AI Technical Summary
In the prior art, when preparing spherical catalysts, the process is complex and energy consumption is large, and continuous production cannot be achieved. The morphology of the catalyst particles is not easy to control, which can easily lead to an increase in fine powder and equipment blockage.
The solid catalyst components are treated with long chain α-olefins, and spherical catalyst components are formed by specific preparation methods, including magnesium, titanium, halogen and internal electron donor compounds, thereby improving the activity and particle shape integrity of the catalyst.
The activity and stereotactic orientation of the catalyst are improved, and the polymer particles produced are highly spherical, high bulk density, narrow particle size distribution, and almost no cracking, crushing, or opening, which is suitable for stable operation of industrial equipment.
Smart Images

Figure CN119874967A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of olefin polymerization, and in particular to an olefin polymerization catalyst component and a preparation method thereof, a catalyst system and application thereof. Background Art
[0002] Because the particle morphology and particle size distribution of polyolefin powder can replicate the particle morphology and particle size distribution of catalyst, and good polymer particle morphology can increase the fluidity of powder, reduce fine powder content, reduce the risk of device clogging, and extend the stable operation time of device. Therefore, catalysts with good particle morphology and narrow particle size distribution are the key directions of polyolefin industry research and development. The adducts of magnesium chloride and alcohol disclosed in patent documents US4421674, US4469648, WO8707620, WO9311166, US5100849, US6020279, US4399054, EP0395383, US6127304 and US6323152, etc., are prepared by methods such as spray drying, spray cooling, high pressure extrusion or high speed stirring. However, these technologies usually have large energy consumption and complex processes, and catalyst components cannot be produced by continuous methods. Patents CN85100997A, CN1097597C, US4952649 and US6323150 use a dissolution precipitation method to prepare a granular catalyst. The characteristic of this method is that the carrier is no longer prepared separately during the catalyst preparation process, but the titanium / magnesium catalyst or catalyst intermediate is precipitated from the solution by co-crystallization. Since the morphology and particle size distribution of this type of catalyst are controlled by the crystallization precipitation process, there are many influencing factors, so the catalyst particle morphology is not easy to control.
[0003] In recent years, the use of emulsification molding technology to prepare spherical catalysts has attracted more and more attention. Patent documents CN1537118, CN101454357, CN103619475, CN107207657 and CN114426597 use emulsification technology to control the crystallization process, and spherical solids are precipitated. The morphology has been greatly improved, but the catalyst still has some shortcomings. Specifically, the resulting polymer particles often cannot replicate the particle morphology of spherical catalysts well, and usually have cracking, crushing, opening and other phenomena, which easily lead to an increase in fine powder, and then cause equipment blockage and transmission pipeline pollution, which is not conducive to the stable operation of the polymerization device. Patent document CN202211326173.3 uses mineral oil to treat the catalyst, which can improve the morphology of polymer particles, but the catalyst activity decreases significantly. Summary of the invention
[0004] In view of the problems existing in the above-mentioned prior art, the present invention has found through experimental exploration that such requirements can be met by treating the solid catalyst component with long-chain α-olefins. Compared with the prior art, the catalyst component of the present invention has higher activity when used for olefin polymerization, and the produced polymer particles have higher sphericity, bulk density and isotactic index, narrower particle size distribution, intact particle shape, and almost no cracking, breaking, opening, etc.
[0005] One of the objects of the present invention is to provide a spherical catalyst component for olefin polymerization, the spherical catalyst component comprising a spherical solid and a long-chain α-olefin compound represented by formula (I); the spherical solid comprises magnesium, titanium, halogen and an internal electron donor compound;
[0006] CH2=CHR a Formula (I)
[0007] Among them, R a It is selected from a straight chain or branched chain alkyl group having 14 to 30 carbon atoms, and a cycloalkyl group having 14 to 30 carbon atoms.
[0008] Alternatively, the long-chain α-olefin compound may be selected from one or more of the following compounds: 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene ....
[0009] Optionally, the internal electron donor compound in the spherical solid object of the present invention is selected from one or more of 2,4-pentanediol dibenzoate, 3,5-heptanediol dibenzoate, 2,3-diisopropyl diethyl succinate, 2,3-diisopropyl diisobutyl succinate, 2,3-diisopropyl di-n-butyl succinate, 2,3-diisopropyl dimethyl succinate, 2,2-dimethyl diisobutyl succinate, 2-ethyl-2-methylsuccinate, 2-ethyl-2-methylsuccinate, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, and 9,9-dimethoxymethylfluorene.
[0010] Optionally, the source of the magnesium element in the present invention is a magnesium compound, and the general formula of the magnesium compound is MgX2, wherein X is a halogen, preferably bromine, chlorine or iodine; specifically, it can be at least one of magnesium dichloride, magnesium dibromide and magnesium diiodide, preferably magnesium dichloride.
[0011] Optionally, the source of the titanium element of the present invention is a titanium compound having a structure TiX' m (OR7) 4-mRepresents, wherein X' is a halogen, R7 is a hydrocarbon group of 1 to 20 carbon atoms, and m is an integer of 1 to 4; preferably at least one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, tetrabutoxytitanium, tetraethoxytitanium, monochlorotriethoxytitanium, dichlorodiethoxytitanium and trichloromonoethoxytitanium, more preferably titanium tetrachloride.
[0012] Optionally, the spherical catalyst component of the present invention, based on a total weight of 100wt%, has a titanium content of 1wt% to 5wt%, a magnesium content of 10wt% to 30wt%, a halogen content of 40wt% to 60wt%, an internal electron donor compound content of 5wt% to 20wt%, and a long-chain α-olefin compound content of 1wt% to 25wt%.
[0013] The second object of the present invention is to provide a method for preparing a spherical catalyst component corresponding to the first object, comprising the following steps:
[0014] S1. contacting a magnesium compound, an organic epoxy compound and an organic phosphorus compound in an organic solvent to form a magnesium-containing solution;
[0015] S2. In the presence of a precipitation aid and optionally a surfactant, the magnesium-containing solution is contacted with a titanium compound and an inert dispersion medium to form a mixture, the mixture is heated, filtered, and washed to obtain a spherical solid;
[0016] S3. The long-chain α-olefin compound represented by formula (I) and the spherical solid are dispersed in an inert diluent and contacted, and the inert diluent is removed by evaporation to obtain a spherical catalyst component;
[0017] CH2=CHR a Formula (I)
[0018] Among them, R a It is selected from a straight chain or branched chain alkyl group having 14 to 30 carbon atoms, and a cycloalkyl group having 14 to 30 carbon atoms.
[0019] Alternatively, the long-chain α-olefin compound may be selected from one or more of the following compounds: 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene ....
[0020] Optionally, the contact conditions in step S3 include: a contact temperature of 0 to 100° C., preferably 20 to 80° C., and a contact time of 0.1 minute to 5 hours, preferably 0.2 minute to 2 hours.
[0021] Optionally, the added volume of the long-chain α-olefin compound per gram of the spherical solid is no more than 1.5 times, preferably 0.3 to 1.0 times, the pore volume of the spherical solid. The pore volume can be determined by BET technology.
[0022] Optionally, the inert diluent is selected from one or more of pentane, isopentane, hexane, heptane and toluene.
[0023] Optionally, the amount of the inert diluent added is not particularly limited. Preferably, the amount of the inert diluent added is 0.1 mL to 100 mL, more preferably 0.5 mL to 50 mL, per gram of the spherical solid.
[0024] Optionally, the evaporation can be carried out under normal pressure, reduced pressure or vacuum conditions; the evaporation temperature is 10°C to 100°C, preferably 20°C to 80°C.
[0025] Optionally, the organic epoxy compound of the present invention is selected from one or more of ethylene oxide, propylene oxide, epichlorohydrin, epichlorohydrin, butylene oxide, butadiene oxide, butadiene dioxide, methyl glycidyl ether and diglycidyl ether, preferably epichlorohydrin.
[0026] Optionally, the organophosphorus compound of the present invention is selected from one or more of trimethyl phosphate, triethyl phosphate, tributyl phosphate, tripentyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, tributyl phosphite, and benzyl phosphite, preferably tributyl phosphate.
[0027] Optionally, the organic solvent of the present invention is an aromatic hydrocarbon compound, specifically one or more of toluene, ethylbenzene, benzene, and xylene, among which toluene is preferred.
[0028] Optionally, the inert dispersion medium of the present invention is selected from one or more of white oil, hexane, heptane, octane, nonane, decane, dodecane, and cyclohexane, preferably one or more of white oil, hexane, and decane.
[0029] Optionally, the precipitation aid of the present invention is selected from one or more of acetic anhydride, phthalic anhydride, succinic anhydride, maleic anhydride, pyromellitic anhydride, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, acetone, methyl ethyl ketone, benzophenone, methyl ether, ethyl ether, propyl ether, butyl ether, and pentyl ether, preferably phthalic anhydride.
[0030] Optionally, the surfactant of the present invention includes one or more selected from alcoholysis products of maleic anhydride polymers and alcoholysis products of maleic anhydride copolymers, preferably one or more selected from alcoholysis products of polymaleic anhydride, alcoholysis products of maleic anhydride-styrene copolymers, alcoholysis products of maleic anhydride-styrene-(meth)acrylate terpolymers, and alcoholysis products of maleic anhydride-(meth)acrylate alkyl ester copolymers.
[0031] The alkyl ester side chains in the maleic anhydride-styrene-(meth)acrylate terpolymer and the maleic anhydride-(meth)acrylate alkyl ester copolymer are independently selected from at least one of a straight or branched alkane group with 1 to 30 carbon atoms, a cycloalkane group with 1 to 30 carbon atoms, and an aromatic hydrocarbon group with 1 to 30 carbon atoms, preferably the above-mentioned substituents with 1 to 20 carbon atoms.
[0032] In the present invention, the alcoholysis product refers to the polymer product obtained by reacting the alcoholysis product with an organic alcohol compound. For example, the organic alcohol compound has a structure of R a OH, where R a It is selected from a straight chain or branched chain alkane group having 2 to 20 carbon atoms, a cycloalkane group having 2 to 20 carbon atoms or an aromatic hydrocarbon group having 2 to 20 carbon atoms.
[0033] Optionally, the surfactant of the present invention further includes at least one of a (meth)acrylic acid alkyl ester polymer and a (meth)acrylic acid alkyl ester copolymer, for example, it may be at least one of a poly (meth)acrylic acid alkyl ester, a (meth)acrylic acid alkyl ester-maleic anhydride copolymer, and a (meth)acrylic acid alkyl ester-maleic anhydride-styrene copolymer; wherein the alkyl ester side chains in the (meth)acrylic acid alkyl ester polymer and the (meth)acrylic acid alkyl ester copolymer are independently selected from a straight or branched alkane group of 1 to 30 carbon atoms, a cycloalkane group of 1 to 30 carbon atoms, or an aromatic hydrocarbon group, preferably the above-mentioned substituents of 1 to 20 carbon atoms.
[0034] The poly(meth)acrylate polymer surfactant of the present invention can be a surfactant product with the trademark T602 purchased from any additive company.
[0035] Optionally, in step S1 of the present invention, the contact method for forming the magnesium-containing solution is not particularly limited. The purpose of the contact is to form a uniform solution containing the magnesium element. The contact conditions include: a contact temperature of 10°C to 100°C, preferably 20°C to 80°C, and a contact time of 0.05 to 10 hours, preferably 0.1 to 6 hours.
[0036] Optionally, in step S2 of the present invention, the inert dispersion medium, the titanium compound and the uniform solution containing the magnesium element may be contacted in any manner, specifically, the inert dispersion medium may be contacted with the uniform solution containing the magnesium element to form a solution, and then the titanium compound may be contacted with the solution to form a mixture; the titanium compound may be contacted with the uniform solution containing the magnesium element to form a solution, and then the inert dispersion medium may be contacted with the solution to form a mixture; the inert dispersion medium and the titanium compound may be mixed evenly and then dripped into the uniform solution containing the magnesium element, or the inert dispersion medium and the titanium compound may be dripped into the uniform solution containing the magnesium element respectively to form a mixture.
[0037] Optionally, in step S2 of the present invention, the contact temperature of the inert dispersion medium, the titanium compound and the magnesium-containing solution is -35 to 60°C, preferably -20 to 40°C; the contact time is 1 minute to 10 hours, preferably 3 minutes to 7 hours.
[0038] Optionally, the mixture formed in step S2 of the present invention includes colloid, two-phase solution, emulsion and other forms.
[0039] Optionally, the preparation method of step S2 of the present invention further includes using one or more methods such as vibration, stirring, atomization, shearing, etc. to promote uniform dispersion of the mixture, further heating the mixture to 50-110°C, solidifying the precipitated solid matter to obtain a suspension, and then stirring the suspension at this temperature or at a higher temperature (not higher than 130°C) for 10 minutes to 24 hours.
[0040] According to the present invention, the temperature raising process of the mixture is not specifically limited, and any known method can be used for the temperature raising, such as slow, stepwise, rapid or programmed temperature raising, and the specific temperature raising method should be adjusted according to the specific formulation, contact temperature, etc. The temperature raising time of the mixture can be 1 minute to 36 hours, preferably 3 minutes to 24 hours.
[0041] Optionally, in the preparation method of the present invention, the surfactant can be added at any position in the preparation method, and can be added as a whole at one time or in parts multiple times. According to the present invention, the surfactant can be added as a whole or in part during or after the formation of the uniform solution containing the magnesium element; can be added as a whole to the inert dispersion medium; or can be added partially to the inert dispersion medium and the other part to the uniform solution containing the magnesium element.
[0042] Optionally, in the preparation method of the present invention, the temperature for adding the surfactant is 0°C to 100°C, preferably 0°C to 80°C, and more preferably 0°C to 60°C.
[0043] Optionally, the preparation method of the present invention further includes the addition of an internal electron donor compound, and the addition position may be any position before step S3, and may be added all at once or in portions multiple times, including being added all or partly to a uniform solution containing the magnesium element; being added all or partly after the mixture is formed and during the solidification, heating and precipitation process; being contacted with the internal electron donor compound all or partly after the spherical solid is precipitated or after the solid is precipitated and filtered and washed.
[0044] Optionally, in the preparation method of the present invention, the internal electron donor compound is added at a temperature of 10°C to 150°C, preferably 10°C to 100°C.
[0045] Optionally, in the preparation method of the present invention, the contact time between the spherical solid and the internal electron donor compound is 0.05 to 8 hours, preferably 1 to 6 hours.
[0046] Optionally, in the preparation method of the present invention, the amount of each component added is calculated per mole of magnesium halide compound, and the organic epoxy compound is 0.1 to 10 moles, the organic phosphorus compound is 0.1 to 10 moles, the organic solvent is 0.5 to 40 moles, the titanium compound is 0.5 to 25 moles, the precipitation aid is 0.01 to 1 mole, and the internal electron donor compound is 0.01 to 1 mole; preferably, the organic epoxy compound is 0.4 to 4 moles, the organic phosphorus compound is 0.8 to 4 moles, the organic solvent is 2 to 30 moles, the titanium compound is 1 to 20 moles, and the precipitation aid is 0.04 to 0.4 moles.
[0047] Optionally, the amount of the inert dispersion medium added is 0.1 g to 300 g, preferably 1 g to 150 g, and the amount of the surfactant added is 0.05 g to 1 g per gram of magnesium halide compound.
[0048] The third object of the present invention is to provide a catalyst system for olefin polymerization corresponding to the above object, the catalyst system comprising:
[0049] (1) a catalyst component; at least one selected from the above-mentioned spherical catalyst components;
[0050] (2) alkyl aluminum compounds; and
[0051] (3) Optionally, an external electron donor compound.
[0052] Optionally, according to the present invention, the alkyl aluminum compound has the general formula AlR' n A compound represented by X"3-n, wherein R' is selected from hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, in particular an alkyl group, an aralkyl group, an aryl group, etc.; X" is a halogen, and n is an integer of 1 to 3.
[0053] Optionally, the alkylaluminum compound is selected from at least one of trimethylaluminum, triethylaluminum, triisobutylaluminum, trioctylaluminum, diethylaluminum monohydrogen, diisobutylaluminum monohydrogen, diethylaluminum monochloride, diisobutylaluminum monochloride, sesquiethylaluminum chloride and ethylaluminum dichloride, preferably triethylaluminum and / or triisobutylaluminum.
[0054] According to the present invention, the amount of the alkyl aluminum compound can be a conventional amount in the art. Preferably, the molar ratio of the aluminum element in the alkyl aluminum compound to the titanium element in the catalyst component is 5 to 5000:1, more preferably 20 to 800:1.
[0055] Optionally, according to the present invention, the external electron donor compound is an organosilicon compound having the general formula R" n' Si(OR y ) 4-n' , wherein n' is an integer of 0 to 3, R" is selected from an alkyl group, a cycloalkyl group, an aryl group, a halogenated alkyl group, a halogen group and a hydrogen atom, and R y One selected from the group consisting of an alkyl group, a cycloalkyl group, an aryl group and a halogenated alkyl group.
[0056] Optionally, the external electron donor compound is selected from at least one of trimethylmethoxysilane, trimethylethoxysilane, trimethylphenoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyltert-butyldimethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, dicyclohexyldimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, methylcyclohexyldimethoxysilane, dicyclopentyldimethoxysilane, 2-ethylpiperidinyl-2-tert-butyldimethoxysilane, (1,1,1-trifluoro-2-propyl)-2-ethylpiperidinyldimethoxysilane, and (1,1,1-trifluoro-2-propyl)-methyldimethoxysilane, preferably methylcyclohexyldimethoxysilane.
[0057] According to the present invention, the amount of the external electron donor compound is not particularly limited. Preferably, the molar ratio of the alkyl aluminum compound to the external electron donor compound is 0.1 to 500:1, preferably 1 to 300:1, and more preferably 3 to 100:1, based on the aluminum content.
[0058] A fourth object of the present invention is to provide an olefin polymerization method corresponding to the above object, the method comprising: contacting one or more olefins with the above catalyst system under olefin polymerization conditions.
[0059] Optionally, at least one of the olefins is an olefin represented by the formula CH2=CHR, wherein R is hydrogen or a C1-C6 straight or branched alkyl group.
[0060] Optionally, the olefin represented by the formula CH2=CHR is one or more of ethylene, propylene, 1-n-butene, 1-n-pentene, 1-n-hexene, 1-n-octene, and 4-methyl-1-pentene.
[0061] Optionally, the olefin is propylene or a copolymer of propylene and other olefins.
[0062] According to the invention, the polymerization of olefins is carried out according to known methods, operating in the liquid phase of the monomer or in the liquid phase of the monomer in an inert solvent, or in the gas phase, or by a combined polymerization process in the gas and liquid phase.
[0063] Optionally, the conditions for olefin polymerization include: a polymerization temperature of 0°C to 150°C, preferably 60°C to 100°C, and a polymerization reaction pressure of 0.1 MPa to 10 MPa, preferably 0.1 MPa to 5 MPa.
[0064] Compared with the prior art, the present invention has at least the following beneficial effects:
[0065] The spherical catalyst component of the present invention has higher activity and stereospecificity when used for propylene polymerization, and the obtained polymer particles have high sphericity, high bulk density, narrow particle size distribution, intact particle shape, and are not easy to be subdivided. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention. In the accompanying drawings:
[0067] Figure 1 This is a physical picture of the olefin polymer produced by the polymerization in Example 1.
[0068] Figure 2 This is a physical picture of the olefin polymer produced by the polymerization in Comparative Example 1. DETAILED DESCRIPTION
[0069] The present invention is described in detail below by way of examples, but the protection scope of the present invention is not limited to the following description.
[0070] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be obtained through commercial channels.
[0071] The test method involved in the embodiment of the present invention is as follows:
[0072] 1. Determination of titanium content in catalyst: Use UV-Vis spectrophotometer 722 for colorimetric determination.
[0073] 2. Magnesium content is measured by magnesium ion and EDTA complexometric titration.
[0074] 3. Determination of the content of internal electron donor compounds in the catalyst: Use chromatography to decompose the catalyst dry powder with dilute acid, extract the internal electron donor compounds with an extractant, and determine them with a liquid chromatograph.
[0075] 4. The content of long-chain α-olefins in the catalyst is calculated based on the dosage and product weight: content of long-chain α-olefins = (weight of catalyst product - weight of spherical solids) / weight of catalyst product × 100 wt%.
[0076] 5. The bulk density (BD) of polymers is determined according to ASTM D1895-96.
[0077] 6. The isotacticity index (II) of propylene polymer is determined by the heptane extraction method: 2 g of dried polymer sample is placed in an extractor and extracted with boiling heptane for 6 hours. The residue is dried to constant weight. The ratio of the obtained polymer weight (g) to 2 (g) is the isotacticity.
[0078] 7. The particle size of the polymer was determined using a Camsizer instrument, D 10 Indicates the particle size (diameter) at which 10% of the particles are smaller than this size, D 50 The particle size at which 50% of the particles are smaller than this size, D 90 SPAN represents the particle size of particles where 90% of the particles are smaller than this size. 90 -D 10 ) / D 50 .
[0079] 8. The sphericity SPHT (ISO9276-6) of the polymer is determined using a Camsizer instrument, SPHT = 4πA / p 2 , P is the circumference of the measured particle projection, and A is the measured area covered by the particle projection. For an ideal sphere, the SPHT value is 1. If it is not an ideal sphere, the SPHT is less than 1. The closer the SPHT value is to 1, the closer the particle is to a sphere.
[0080] 9. The symmetry Symm of the polymer is determined using a Camsizer instrument, Symm = (1 + min (r1 / r2)) / 2, where r1 and r2 are the distances from the center of the region to the boundary in the measurement direction. For asymmetric particles, Symm is less than 1. If the center of the region is outside the particle, Symm is less than 0.5. "Symm" is the minimum value of a set of symmetry values measured from different directions.
[0081] 10. The aspect ratio B / L of the polymer is determined using a Camsizer instrument, B / L = X c min / X Fe max , where X c min and X Fe max Value in X c and X Fe outside the measurement set of values.
[0082] Example 1
[0083] (1) Preparation of catalyst components
[0084] In a 1L reactor that has been repeatedly replaced with high-purity nitrogen, 10.8g of anhydrous magnesium chloride, 75mL of toluene, 9.6mL of epichlorohydrin, and 42mL of tributyl phosphate were added in sequence, and stirred at 300RMP for 2 hours at 60°C. Then 3.3g of phthalic anhydride was added and maintained at 60°C for another hour. The temperature was lowered to 40°C, and a mixture of 129mL of decane and 5.7g of T602 was added, and the stirring was increased to 400RMP and maintained for another hour. Then the solution was cooled to 10°C, and 114mL of titanium tetrachloride was added dropwise. After the addition was completed, it was maintained for another hour. The temperature was gradually raised to 80°C within 3 hours and maintained for 1 hour. 1.4mL of 2-isopropyl-2-isopentyl-1,3-dimethoxypropane was added during the heating process. After filtering the mother liquor, the solid was washed twice with 200mL of toluene. Add 120 mL of toluene and 80 mL of titanium tetrachloride, treat at 110°C for 0.5 hour, and remove the filtrate. Add 120 mL of toluene and 80 mL of titanium tetrachloride, treat at 110°C for 0.5 hour, and remove the filtrate. After repeated washing with 200 mL of hexane for 4 times, spherical solid a1 is obtained after drying. The titanium content of the obtained spherical solid a1 is 2.0 wt%, the magnesium content is 18.5 wt%, and the 2-isopropyl-2-isopentyl-1,3-dimethoxypropane content is 10.8 wt%. The specific surface area of the spherical solid a1 is 420.2 m 2 / g, and the pore volume is 0.287cm3 / g.
[0085] 5.0 g of spherical solid a1, 1.4 mL of 1-octadecene and 5 mL of hexane were placed in a 240 mL reactor, and the mixture was stirred thoroughly. The hexane was evaporated under a nitrogen atmosphere to obtain a catalyst component A1. The 1-octadecene content in the obtained catalyst component A1 was 18.0 wt%.
[0086] (2) Propylene polymerization
[0087] In a 5-liter autoclave, after nitrogen is fully replaced, 5 mL of triethylaluminum hexane solution (the concentration of triethylaluminum is 0.5 mmol / mL), 1 mL of cyclohexylmethyldimethoxysilane (CHMMS) hexane solution (the concentration of CHMMS is 0.1 mmol / mL), 10 mL of anhydrous hexane and 10 mg of solid catalyst component A1 are added at room temperature. The autoclave is closed, and 4.5 L of hydrogen and 2.3 L of liquid propylene are added. The temperature is raised to 70°C, and the polymerization reaction is carried out at 70°C for 1 hour. After the reaction is completed, the reactor is cooled and stirring is stopped, and the reaction product is discharged to obtain an olefin polymer. The actual product is as follows: Figure 1 The catalyst polymerization data and olefin polymer data are shown in Table 1.
[0088] Example 2
[0089] (1) Preparation of catalyst components
[0090] 5.0 g of the spherical solid a1 prepared in Example 1, 0.7 mL of 1-octadecene and 5 mL of hexane were placed in a 240 mL reactor, and the mixture was stirred thoroughly. The hexane was evaporated under a nitrogen atmosphere to obtain a catalyst component A2. The 1-octadecene content in the obtained catalyst component A2 was 10.0 wt%.
[0091] (2) Propylene polymerization
[0092] The polymerization conditions were the same as in Example 1, using solid catalyst component A2. The polymerization data and olefin polymer data are shown in Table 1.
[0093] Example 3
[0094] (1) Preparation of catalyst components
[0095] 5.0 g of the spherical solid a1 prepared in Example 1, 1.4 mL of 1-hexadecene and 10 mL of hexane were placed in a 240 mL reactor and the mixture was stirred thoroughly. The hexane was evaporated under a nitrogen atmosphere to obtain a solid catalyst component A3. The 1-hexadecene content in the obtained catalyst component A3 was 17.5 wt%.
[0096] (2) Propylene polymerization
[0097] The polymerization conditions were the same as in Example 1, using solid catalyst component A3. The polymerization data and olefin polymer data are shown in Table 1.
[0098] Example 4
[0099] (1) Preparation of catalyst components
[0100] 5.0 g of the spherical solid a1 prepared in Example 1, 1.4 mL of 1-eicosene and 5 mL of hexane were placed in a 240 mL reactor and the mixture was stirred thoroughly. The hexane was evaporated under a nitrogen atmosphere to obtain a solid catalyst component A4. The 1-eicosene content in the obtained catalyst component A4 was 18.0 wt%.
[0101] (2) Propylene polymerization
[0102] The polymerization conditions were the same as in Example 1, using solid catalyst component A4. The polymerization data and olefin polymer data are shown in Table 1.
[0103] Example 5
[0104] (1) Preparation of catalyst components
[0105] 5.0 g of the spherical solid a1 prepared in Example 1, 1.4 mL of 1-tetradecene and 5 mL of hexane were placed in a 240 mL reactor and the mixture was stirred thoroughly. The hexane was evaporated under a nitrogen atmosphere to obtain a solid catalyst component A5. The 1-tetradecene content in the obtained catalyst component A5 was 16.4 wt%.
[0106] (2) Propylene polymerization
[0107] The polymerization conditions were the same as in Example 1, using solid catalyst component A5. The polymerization data and olefin polymer data are shown in Table 1.
[0108] Comparative Example 1
[0109] The spherical solid a1 prepared in Example 1 was directly subjected to propylene polymerization. The polymerization conditions were the same as in Example 1. The polymerization data and olefin polymer data are shown in Table 1. The olefin polymer is shown in Table 1. Figure 2 shown.
[0110] Comparative Example 2
[0111] (1) Preparation of catalyst components
[0112] 5.0 g of the spherical solid a1 prepared in Example 1, 1.4 mL of octadecane and 5 mL of hexane were placed in a 240 mL reactor and the mixture was stirred thoroughly. The hexane was evaporated under a nitrogen atmosphere to obtain 6.1 g of a solid catalyst component D1. The octadecane content in the obtained catalyst component D1 was 18.0 wt%.
[0113] (2) Propylene polymerization
[0114] The polymerization conditions were the same as in Example 1, using solid catalyst component D1. The polymerization data and olefin polymer data are shown in Table 1.
[0115] Comparative Example 3
[0116] (1) Preparation of catalyst components
[0117] 5.0 g of the spherical solid a1 prepared in Example 1, 1.4 mL of 1-hexene and 5 mL of hexane were placed in a 240 mL reactor and the mixture was stirred thoroughly. The hexane was evaporated under a nitrogen atmosphere to obtain 5.0 g of a solid catalyst component D2. The 1-hexene content in the obtained catalyst component D2 was 0.9 wt%.
[0118] (2) Propylene polymerization
[0119] The polymerization conditions were the same as in Example 1, using solid catalyst component D2. The polymerization data and olefin polymer data are shown in Table 1.
[0120] Table 1.
[0121]
[0122] According to the above examples and comparative examples, in the preparation method of the present invention, by using a long-chain α-olefin compound to treat the spherical solid, the catalyst component activity and stereospecificity are higher, the sphericity and bulk density of the obtained polymer powder are higher, and the powder D 10 The particle size distribution is narrower, and there is almost no cracking, breaking or opening, which is suitable for industrial equipment operation.
[0123] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed minimum and maximum values are considered to have been disclosed.
[0124] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A spherical catalyst component for olefin polymerization, characterized in that The spherical catalyst component comprises a spherical solid and a long-chain α-olefin compound represented by formula (I); The spherical solid object comprises magnesium element, titanium element, halogen and an internal electron donor compound; CH2=CHR a Formula (I) Among them, R a It is selected from a straight chain or branched chain alkyl group having 14 to 30 carbon atoms, and a cycloalkyl group having 14 to 30 carbon atoms.
2. The spherical catalyst component according to claim 1, characterized in that The long-chain α-olefin compound is selected from at least one of 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 1-eicosene, 1-eicosene, 1-eicosene, 1-tetracosene, and 1-hexacosene; And / or, the internal electron donor compound is selected from at least one of 2,4-pentanediol dibenzoate, 3,5-heptanediol dibenzoate, diethyl 2,3-diisopropylsuccinate, diisobutyl 2,3-diisopropylsuccinate, di-n-butyl 2,3-diisopropylsuccinate, dimethyl 2,3-diisopropylsuccinate, diisobutyl 2,2-dimethylsuccinate, diisobutyl 2-ethyl-2-methylsuccinate, diethyl 2-ethyl-2-methylsuccinate, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, and 9,9-dimethoxymethylfluorene; And / or, the source of the magnesium element is a magnesium compound, the general formula of the magnesium compound is MgX2, wherein X is a halogen, preferably bromine, chlorine or iodine; the magnesium compound is preferably at least one of magnesium dichloride, magnesium dibromide and magnesium diiodide; And / or, the source of the titanium element is a titanium compound, and the general formula of the titanium compound is TiX' m (OR7) 4-m , wherein X' is a halogen, R7 is a hydrocarbon group of 1 to 20 carbon atoms, and m is an integer of 1 to 4; the titanium compound is preferably at least one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, tetrabutoxytitanium, tetraethoxytitanium, monochlorotriethoxytitanium, dichlorodiethoxytitanium and trichloromonoethoxytitanium.
3. The spherical catalyst component according to claim 1 or 2, characterized in that Based on the total weight of the spherical catalyst component (100wt%), the content of titanium is 1wt% to 5wt%, the content of magnesium is 10wt% to 30wt%, the content of halogen is 40wt% to 60wt%, the content of internal electron donor compound is 5wt% to 20wt%, and the content of long-chain α-olefin compound is 1wt% to 25wt%.
4. A method for preparing a spherical catalyst component, characterized in that: The following steps are involved: S1. contacting a magnesium compound, an organic epoxy compound and an organic phosphorus compound in an organic solvent to form a magnesium-containing solution; S2. In the presence of a precipitation aid and optionally a surfactant, the magnesium-containing solution is contacted with a titanium compound and an inert dispersion medium to form a mixture, the mixture is heated, filtered, and washed to obtain a spherical solid; S3. The long-chain α-olefin compound represented by formula (I) and the spherical solid are dispersed in an inert diluent and contacted, and the inert diluent is evaporated to obtain a spherical catalyst component; CH2=CHR a Formula (I) Among them, R a It is selected from a straight chain or branched chain alkyl group having 14 to 30 carbon atoms, and a cycloalkyl group having 14 to 30 carbon atoms.
5. The preparation method according to claim 4, characterized in that: The long-chain α-olefin compound is selected from at least one of 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 1-eicosene, 1-eicosene, 1-eicosene, 1-tetracosene, and 1-hexacosene; and / or, the added volume of the long-chain α-olefin compound per gram of the spherical solid is no more than 1.5 times, preferably 0.3 to 1.0 times, the pore volume of the spherical solid; and / or, the inert diluent is selected from at least one of pentane, isopentane, hexane, heptane and toluene; and / or, the amount of the inert diluent added is 0.1 mL to 100 mL, preferably 0.5 mL to 50 mL, per gram of the spherical solid; And / or, the evaporation is carried out under normal pressure, reduced pressure or vacuum, and the evaporation temperature is 10°C to 100°C, preferably 20°C to 80°C; and / or, the organic epoxy compound is at least one selected from ethylene oxide, propylene oxide, epichlorohydrin, epichlorohydrin, butylene oxide, butadiene oxide, butadiene dioxide, methyl glycidyl ether and diglycidyl ether; And / or, the organophosphorus compound is at least one selected from trimethyl phosphate, triethyl phosphate, tributyl phosphate, tripentyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, tributyl phosphite, and benzyl phosphite; And / or, the organic solvent is an aromatic hydrocarbon compound, preferably at least one of toluene, ethylbenzene, benzene and xylene; and / or, the inert dispersion medium is selected from at least one of white oil, hexane, heptane, octane, nonane, decane, dodecane and cyclohexane; and / or, the precipitation aid is selected from at least one of acetic anhydride, phthalic anhydride, succinic anhydride, maleic anhydride, pyromellitic anhydride, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, acetone, methyl ethyl ketone, benzophenone, methyl ether, ethyl ether, propyl ether, butyl ether and pentyl ether; And / or, the surfactant comprises one or more selected from alcoholysis products of maleic anhydride polymers and alcoholysis products of maleic anhydride copolymers, preferably at least one selected from alcoholysis products of polymaleic anhydride, alcoholysis products of maleic anhydride-styrene copolymers, alcoholysis products of maleic anhydride-styrene-(meth)acrylate terpolymers and alcoholysis products of maleic anhydride-(meth)acrylate alkyl ester copolymers; The alkyl ester side chains in the maleic anhydride-styrene-(meth)acrylate terpolymer and the maleic anhydride-(meth)acrylate alkyl ester copolymer are independently selected from at least one of a linear or branched alkane group with 1 to 30 carbon atoms, a cycloalkane group with 1 to 30 carbon atoms, and an aromatic hydrocarbon group with 1 to 30 carbon atoms, and are preferably at least one of a linear or branched alkane group with 1 to 20 carbon atoms, a cycloalkane group with 1 to 20 carbon atoms, and an aromatic hydrocarbon group with 1 to 20 carbon atoms; Preferably, the surfactant further comprises at least one of a (meth)acrylic acid alkyl ester polymer and a (meth)acrylic acid alkyl ester copolymer, and more preferably at least one of a poly (meth)acrylic acid alkyl ester, a (meth)acrylic acid alkyl ester-maleic anhydride copolymer, and a (meth)acrylic acid alkyl ester-maleic anhydride-styrene copolymer; wherein the alkyl ester side chains in the (meth)acrylic acid alkyl ester polymer and the (meth)acrylic acid alkyl ester copolymer are independently selected from a linear or branched alkyl group having 1 to 30 carbon atoms, a cycloalkyl group having 1 to 30 carbon atoms, or an aromatic group, and are preferably at least one of a linear or branched alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 1 to 20 carbon atoms, and an aromatic group having 1 to 20 carbon atoms.
6. The preparation method according to claim 4 or 5, characterized in that: In step S1, the contact conditions include: a contact temperature of 10°C to 100°C, preferably 20°C to 80°C, and a contact time of 0.05 to 10 hours, preferably 0.1 to 6 hours; And / or, in step S2, the contact temperature of the inert dispersion medium, the titanium compound and the magnesium-containing solution is -35 to 60° C., preferably -20 to 40° C.; the contact time is 1 minute to 10 hours, preferably 3 minutes to 7 hours; And / or, in step S2, the temperature treatment comprises: heating the mixture to 50-110° C., solidifying and precipitating spherical solids to obtain a suspension, and stirring the suspension at 50-130° C. for 10 minutes to 24 hours; the temperature treatment time is 1 minute to 36 hours, preferably 3 minutes to 24 hours; And / or, the surfactant is added at a temperature of 0°C to 100°C, preferably 0°C to 80°C, and more preferably 0°C to 60°C; And / or, in step S3, the contact conditions include: a contact temperature of 0 to 100° C., preferably 20 to 80° C., and a contact time of 0.1 minute to 5 hours, preferably 0.2 minute to 2 hours; And / or, the preparation method further comprises adding an internal electron donor compound, and the internal electron donor compound is added at any position before step S3; and / or, the internal electron donor compound is added at a temperature of 10°C to 150°C, preferably 10°C to 100°C; And / or, the contact time between the spherical solid and the internal electron donor compound is 0.05 to 8 hours, preferably 1 to 6 hours. And / or, the amount of each component added is calculated per mole of magnesium halide compound, the organic epoxy compound is 0.1 to 10 moles, the organic phosphorus compound is 0.1 to 10 moles, the organic solvent is 0.5 to 40 moles, the titanium compound is 0.5 to 25 moles, the precipitation aid is 0.01 to 1 mole, and the internal electron donor compound is 0.01 to 1 mole; preferably, the organic epoxy compound is 0.4 to 4 moles, the organic phosphorus compound is 0.8 to 4 moles, the organic solvent is 2 to 30 moles, the titanium compound is 1 to 20 moles, and the precipitation aid is 0.04 to 0.4 moles; And / or, per gram of magnesium halide compound, the added amount of the inert dispersion medium is 0.1 g to 300 g, preferably 1 g to 150 g, and the added amount of the surfactant is 0.05 g to 1 g.
7. A catalyst system for olefin polymerization, characterized in that: The catalyst system comprises: (1) Catalyst component; at least one selected from the group consisting of the spherical catalyst component described in any one of claims 1 to 3 and the spherical catalyst component prepared by the preparation method described in any one of claims 4 to 6; (2) alkyl aluminum compounds; and (3) Optionally, an external electron donor compound.
8. The catalyst system according to claim 7, characterized in that The alkyl aluminum compound is of the general formula AlR' n X" 3-n The compound shown, wherein R' is selected from hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, preferably an alkyl group, an aralkyl group, or an aryl group; X" is a halogen, and n is an integer of 1 to 3; Preferably, the alkyl aluminum compound is selected from at least one of trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, trioctylaluminum, diethyl aluminum monohydrogenate, diisobutyl aluminum monohydrogenate, diethyl aluminum monochloride, diisobutyl aluminum monochloride, sesquiethyl aluminum chloride and ethyl aluminum dichloride; and / or, the molar ratio of the aluminum element in the alkyl aluminum compound to the titanium element in the catalyst component is 5 to 5000:1, more preferably 20 to 800:1; And / or, the external electron donor compound is an organosilicon compound, the general formula of which is R" n' Si(OR y ) 4-n' , wherein n' is an integer of 0 to 3, R" is selected from an alkyl group, a cycloalkyl group, an aryl group, a halogenated alkyl group, a halogen group and a hydrogen atom, and R y One selected from the group consisting of an alkyl group, a cycloalkyl group, an aryl group, and a halogenated alkyl group; Preferably, the external electron donor compound is selected from at least one of trimethylmethoxysilane, trimethylethoxysilane, trimethylphenoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyltert-butyldimethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, dicyclohexyldimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, methylcyclohexyldimethoxysilane, dicyclopentyldimethoxysilane, 2-ethylpiperidinyl-2-tert-butyldimethoxysilane, (1,1,1-trifluoro-2-propyl)-2-ethylpiperidinyldimethoxysilane, and (1,1,1-trifluoro-2-propyl)-methyldimethoxysilane; And / or, based on the aluminum content, the molar ratio of the alkyl aluminum compound to the external electron donor compound is 0.1 to 500:1, preferably 1 to 300:1, and more preferably 3 to 100:
1.
9. An olefin polymerization method, characterized in that: The method comprises contacting one or more olefins with the catalyst system of claim 7 or 8 under olefin polymerization conditions.
10. The method according to claim 9, characterized in that At least one of the olefins is an olefin represented by the formula CH2=CHR, wherein R is hydrogen or a C1-C6 straight or branched alkyl group; Preferably, the olefin represented by the formula CH2=CHR is at least one of ethylene, propylene, 1-n-butene, 1-n-pentene, 1-n-hexene, 1-n-octene, and 4-methyl-1-pentene; Preferably, the olefin is propylene or a copolymer of propylene and other olefins; And / or, the conditions for olefin polymerization include: polymerization reaction temperature of 0°C to 150°C, preferably 60°C to 100°C, and polymerization reaction pressure of 0.1MPa to 10MPa, preferably 0.1MPa to 5MPa.
Citation Information
Patent Citations
Preparation method of olefin polymerization catalyst component and prepared olefin polymerization catalyst component
CN114426597A
Polyolefin catalysts and method of preparing an olefin polymer
US5135995A